Investigation of corrugated profiles in thin lossy dielectric slabs for wideband absorption up to 100 GHz - Huynen, Isabelle (Frontiers in Materials, 2022)
The paper compares and optimizes through modeling conductive polymer composite slabs having different architectures of corrugated surfaces, designed to minimize both the reflectivity and its sensitivity to the angle of incidence of a microwave/millimeter wave signal impinging on the corrugated surface of the slab. Simulations using CST Studio software consider Poly-Lactid-Acid as dielectric material since it is widely used for 3D printing and offers very good possibilities of recycling in the frame of sustainability and green processing. Various profiles of corrugation are investigated; triangular, sinusoidal, or square-dot profiles, and compared with a uniform profile. Parameters such as height, width, and periodicity of the corrugations are varied in order to optimize the performances in terms of reflectivity over a large range of frequencies, between 20 GHz and 100 GHz. The configuration considered is the reflective screen, when the corrugated lossy dielectric slab covers a metallic plate mimicking the target. The goal is to maintain the reflectivity below 10 dB, in order to ensure up to 95% of absorption, for incidence angles up to 60°. Guidelines for the design and optimization of corrugated dielectric slab absorbers are proposed using specific gauges (Rozanov formalism and figure of merit) for the assessment of performances. Particular attention is devoted to the feasibility of manufacturing corrugated structures using additive 3D printing techniques.